Elaboration and validity of the Instrumento para Avaliação de Modelos metodológicos voltados ao Desenvolvimento de Tecnologias - Cléton Salbego; Elisabeta Albertina Nietsche; Patrícia Bitencourt Toscani Greco; Nara Marilene Oliveira Girardon-Perlini; Silvana Bastos Cogo; Tierle Kosloski Ramos; Andrei Pompeu Antunes (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to elaborate and validate the Instrumento para Avaliação de Modelos metodológicos voltados ao Desenvolvimento de Tecnologias. Methods: a methodological study, developed in three stages: instrument structuring through documentary research and researchers' expertise; instrument validity with a panel of 11 expert judge nurses; and instrument final composition. Results: the instrument, after validity by experts, consisted of 30 items, divided into the content (26 items) and appearance (four items) domains. In the initial instrument validity process, 11 items were modified and seven were withdrawn, as they had a percentage of agreement below 0.80. The instrument showed excellent internal consistency, with values greater than 0.90 in its psychometric criteria. Conclusion: the instrument produced and validated aimed at assessing research methodological models for technological development showed good reliability, and may contribute to the methodological rigor of technological development research in nursing.